An investigation on the behavior of a new connection for precast structures under reverse cyclic loading. (15th August 2018) - Lu, Cong; Dong, Bingqing; Pan, Jinlong; Shan, Qifeng; Hanif, Asad; Yin, Wanyun
Highlights: A novel precast beam-column connection with U-shaped bars and ECC is proposed. Seven specimens were tested under reverse cyclic loading. Seismic behavior of the connections are compared and discussed. Connections incorporating ECC have shown advantages in various aspects. Abstract: This paper aims to develop a new precast beam-column connection with U-shaped bars and ECC materials, which eliminates the need for formworks, welding and bolting. In this paper, an experimental study of five precast and two monolithic connections, including exterior and interior connections under reverse cyclic loading, will be carried out. All specimens were evaluated by their failure mode, hysteresis characteristics, stiffness degradation, ductility and energy dissipation under reverse cyclic loading. The proposed connection using high strength concrete exhibited more satisfactory seismic behavior than the cast-in-place construction in terms of hysteretic behavior, stiffness degradation and energy dissipation, while their load-carrying capacity and ductility were slightly lower. When ECC material is incorporated, these precast connections showed improved load-carrying capacity and ultimate displacement compared with the precast connections using concrete. Their seismic performance is comparable to (even better at certain aspects) the conventional cast-in-place connections and is therefore recommended for the applications in the high seismic region.